High aspect ratio nanoholes in glass generated by femtosecond laser pulses with picosecond intervals. (February 2018) - Ahn, Sanghoon; Choi, Jiyeon; Noh, Jiwhan; Cho, Sung-Hak
Highlights: High aspect ratio (>13) nanoholes are fabricated by femtosecond laser. The diameter of nanoholes are 250∼350 nm and depth of it are 4∼6 µm. We reveal that a temporal change of electron density affects to a shape of nanohole. Abstract: Because of its potential uses, high aspect ratio nanostructures have been interested for last few decades. In order to generate nanostructures, various techniques have been attempted. Femtosecond laser ablation is one of techniques for generating nanostructures inside a transparent material. For generating nanostructures by femtosecond laser ablation, previous studies have been attempted beam shaping such as Bessel beam and temporal tailored beam. Both methods suppress electron excitation at near surface and initiate interference of photons at certain depth. Recent researches indicate that shape of nanostructures is related with temporal change of electron density and number of self-trapped excitons. In this study, we try to use the temporal change of electron density induced by femtosecond laser pulse for generating high aspect ratio nanoholes. In order to reveal the effect of temporal change of electron density, secondary pulses are irradiated from 100 to 1000 ps after the irradiation of first pulse. Our result shows that diameter of nanoholes is increasing and depth of nanoholes is decreasing as pulse to pulse interval is getting longer. With manipulating of pulse to pulse interval, we could generate high aspect ratio nanoholes with diameter of 250–350 nm and depth of 4∼6 µm inside a glass.